Influence of Remineralizing Gels on Bleached Enamel Microhardness In Different Time Intervals - Borges, Alessandra Buhler [UNESP]; Yui, K. C. K. [UNESP]; D'Avila, T. C.; Takahashi, C. L.; Torres, C. R. G. [UNESP]; Borges, Alexandre Luiz Souto [UNESP] (Operative Dentistry Inc, 2010)
This study evaluated the influence of bleaching gel pH, the effect of applying remineralizing gels after bleaching and the effect of artificial saliva on enamel microhardness. Seventy bovine inci-sors were divided into three groups: Group 1 (n=10) received no bleaching procedure (control); Group 2 was bleached with a 35% hydrogen peroxide neutral gel (n=30) and Group 3 was bleached with a 35% hydrogen peroxide acid gel (n=30). Each experimental group was subdivided into three groups (n=10) according to the post-bleaching treatment: storage in artificial saliva, application of a fluoride gel and application of a combination of calcium and fluoride gel. The specimens were stored in artificial saliva for 7, 15 and 30 days and enamel microhardness was evaluated. The Vickers microhardness data were analyzed by three-way RM ANOVA, which revealed a significant difference only for treatment factor. The Tukey's test showed that the groups bleached followed by no additional treatment exhibited microhardness means significantly lower than the bleached groups treated with remineralizing gels. The Dunnet's test showed a significant difference only for the group bleached with acid gel without remineralizing treatment compared to the control group measured immediately after bleaching. It was concluded that acid bleaching gel significantly reduced enamel microhardness and that use of remineralizing gels after bleaching can significantly enhance the microhardness of bleached enamel.